Marketing and Institutional Characteristics of Dairy Industry In Indonesia - Guntoro, Budi; Widyobroto, Budi Prasetyo; Umami, Nafiatul; Indratiningsih; Nurtini, Sudi; Pertiwiningrum, Ambar; Rochijan (2016)
The aim of this study was to map comprehensively as the basis for the implementation of technologies that met the needs of dairy farmers. Specifically, the objectives were : to analyze the marketing and institutional characteristics of dairy industry in rural farmers. The target population is dairy farmers in Central Java, Yogyakarta and East Java Provinces. The numbers of samples were selected in nine dairy cooperatives, which were three cooperatives represented each province, three milk processing industries, and totally 270 farmers as respondents. Data were taken such as demographic characteristic of farmers, farmer groups, and marketing line of milk distribution from farmers to consumers. The results showed that the institutional environment of dairy industry and governance both from Central Java, Yogyakarta and East Java need handlers more serious, it can be seen from the dependence of farmers on the institutions that exist including cooperatives and milk processing industries still high. From the aspect of livestock farming, cows in East java showed better performance than the two other major regions, namely Central Java and Yogyakarta. Distribution and marketing of milk which is currently still depends on the institutional binding of cooperative, and dairy processing industry, and there has been no increase of participation in enhancing the value chain